How deep is your love? Innovation, Upgrading and the Depth of Internationalization - Birgit Meyer (ZBW - Leibniz Information Centre for Economics, 2020)
Global Value Chains (GVCs) provide an important opportunity to become member of the global economy. Gaining access to GVCs and the possibility of developing linkages with major suppliers and customers enables the prospect to upgrade products and production processes via knowledge and technological spillovers, learning by doing and the allocation of new task. Adopting new production technologies and realizing synergy effects might allow cost reduction, product innovation and product upgrading. Even if GVCs represent a rich environment for innovation activities, the extent to which knowledge is created and transferred among firms may vary considerably across their mode of participation in the global chain, thus resulting in heterogeneous innovation capacities for the firms involved. Differences in the forms of governance underlying buyer-supplier relationships - for instance linked to dissimilar power asymmetries and firm capability - can strongly affect the knowledge transmission along the chains and are potentially able to explain heterogeneities in firms' innovation propensity. Using a firm-product-level dataset of Indian manufacturing firms including information on business groups, this paper contributes to recent studies on international production and GVCs by testing the effect of different modes of internationalization on firms' upgrading activities, including the extensive and intensive margins of innovation and R&D expenditures. Controlling for the selection bias associated with the chosen mode of internationalization and accounting for potential reverse causality, this paper shows that the deeper firms are integrated internationally, the higher the likelihood that they engage in innovation activities. Firms which have a high mode of internationalization are not only more productive, but also more likely to introduce new products, upgrade existing products and produce more sophisticated products than firms that are less engaged in international markets and, thus, less prone to international competition.
Keywords: F23; F61; O31; D22; L23; F14; 330; Global value chain; exporting; importing; FDI; innovation; upgrading